Campomelic dysplasia: a case report - Meshram, Rajkumar M.; Ambatkar, Kanchan; Gite, Renuka (International Journal of Contemporary Pediatrics, 2024)
Campomelic dysplasia is a rare, lethal, and autosomal dominant inherited disorder with reversal of sex in genotypic male in two third cases. An eight-month-old phenotypic female infant was admitted with respiratory distress and failure to thrive. She had facial dysmorphism, cleft in soft palate, pectus excavatum deformity, bowing of lower limbs, dimpling at right knee area and bilateral congenital talipes equinovarus deformity. Radiographs shows 11 pairs of ribs, hypoplastic scapula, bowing of bilateral tibia and hypoplastic bilateral fibula. Karyotyping was 46XYchromosome and whole exome sequencing reveals autosomal dominant affecting SOX9 (NM_000346.4) gene, pathogenic variant of c.583C>T (p.Gin195Ter) which is stop gained variant. She was managed according to hospital protocol and discharged. Prenatal diagnosis, genetic counselling and multidisciplinary approach for management of survival cases is important to reduce mortality.